Mineralogical Characteristics Of Ieropigi-Kastoria Laterites, Northern Greece - A. Iordanidis (Society for Mining, Metallurgy & Exploration, 2006)
Ieropigi Fe-Ni deposit is located in northern Greece, in Kastoria?s prefecture near Albania?s borders. A laterite profile exposed by opencast mining and placed near the basement of the mine was chosen for sampling. Ten samples, representing ?pure? Fe-Ni ore, ophiolite-bedrock, ?red? ophiolite and ?enriched? ophiolite were collected, based on macroscopic observation. The samples were analysed by X-Ray powder Diffraction (XRD) for the determination of the mineral phases. Iron and Nickel concentrations of the same samples were also determined by X-Ray Fluorescence (XRF) methodology. The Fe-Ni ore samples consists predomi-nantly of hematite, goethite, chrysotile (serpentine), saponite and quartz. ?Red? ophiolite samples consists mainly of chrysotile, hematite, quartz, calcite and small amounts of paragonite and goethite. Bedrock and ?enriched ophiolite samples are comprised of chrysotile, hematite, calcite, quartz, nontronite, paragonite and sepiolite. The Fe content ranges between 13% and 49% in Fe-Ni ore samples and between 7% and 10% in ophiolite samples. The Ni content ranges between 1% and 3% in Fe-Ni ore samples and between 0.3% and 4.5% in ophiolite samples (the higher content is observed in the so-called ?enriched? ophiolite). A correlation between Fe-Ni concentrations and mineral assemblages is being attempted in order to evaluate the nickel-rich mineral phases. It is shown that the nickeliferous minerals are serpentine, hematite, goethite and saponite.